The Influence of Snake-Ladder Game toward Early Childhood Children’s Mathematics Skills - Chayati, Nur; Sugiyo, Sugiyo; Sulistiyorini, Sri (Universitas Negeri Semarang, 2021)
Low learning media and conventional method implementations made less maximum learning to improve children’s mathematics skills. This research aims to analyze the cooperative learning model with snake-ladder game media toward early childhood children's mathematics skills. The applied method was the experimental method with a pretest-posttest group control design. The population consisted of 135 children aged 5-6 years old and by the applying purposive sampling 30 Children were chosen as samples. This research used mathematics skill observation with a 1-4 Likert scale to collect the data. By employing t-test is used the effect of the snake and ladder game on math skills was analyzed. The results showed that there was a sig value of 0.00 < 0.05, which means that there was a difference in the increase of the math abilities of children aged 5-6 years by implementing snake and ladder media. The results showed that the cooperative learning model assisted by the snake-ladder game was effective to improve learners’ mathematics skill outcomes. It proved that a cooperative learning method assisted by a snake-ladder game could improve the mathematics skills of learners aged 5-6 years old.